2009
DOI: 10.1177/112972980901000311
|View full text |Cite
|
Sign up to set email alerts
|

Should Fistulas Really be First in the Elderly Patient?

Abstract: This data suggest in the elderly patients, autogenous fistulas may not be the best option for this set of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 9 publications
1
108
3
Order By: Relevance
“…Answer AVF nonmaturation or early failure is associated with older age, female sex, forearm location, and cardiovascular disease (57)(58)(59)(60). In contrast, no clinical factors have been associated with early AVG failure.…”
Section: James C Harms Md (Nephrology Fellow At University Of Alabamentioning
confidence: 99%
“…Answer AVF nonmaturation or early failure is associated with older age, female sex, forearm location, and cardiovascular disease (57)(58)(59)(60). In contrast, no clinical factors have been associated with early AVG failure.…”
Section: James C Harms Md (Nephrology Fellow At University Of Alabamentioning
confidence: 99%
“…Comorbidities, functional status, life expectancy, and social factors should play a major role in the decision-making process. To determine if fistulas should be the preferred option in elderly patients, Richardson et al analyzed outcomes after AVF surgery in 48 elderly patients and reported only eight AVFs being accessed for dialysis, suggesting that, despite K/DOQI guidelines (which do not have recommendations for specific age groups), AVFs may not be the best option in patients over 70 years of age (25). Another study found that the intervention and survival rates were similar among older (Ͼ65 years old) and younger (Ͻ65) dialysis patients after radiocephalic and brachiocephalic AVF.…”
Section: Should Avf Be Chosen For Access In All Elderly Patients?mentioning
confidence: 99%
“…A recent study illustrated in stark details how advanced age might affect clinical judgment regarding choice of vascular access (45). This observational study compared fistula and patient survival in dialysis-dependent patients older or younger than 70 years of age.…”
mentioning
confidence: 99%